Workplace spirituality and employee commitment: The role of emotional intelligence and organisational citizenship behaviour in Indian organisations. Issue 3 (9th April 2018) - Jena, Lalatendu Kesari; Pradhan, Sajeet
Abstract : Purpose: The purpose of this paper is to provide an empirical investigation of workplace spirituality (WS) and employee commitment (EC). EC is presumed as a mindset which is generally influenced by spiritual culture and the prospective outcomes are in the form of sense of calling and sense of membership with one's profession and organisation. Drawing on the proposition of Tepper's (2003), organisational citizenship behaviour (OCB) was proposed as a mediator between spirituality and commitment. The study also tests whether emotional intelligence (EI) moderates the relations among them. Design/methodology/approach: Data were collected from 761 executives working in Indian manufacturing and service organisations. SPSS 20.0 and AMOS 18.0 were used to analyse the data. Findings: The results confirmed that an insignificant mediation of OCB and moderation of EI among WS and EC. However, WS is found to be a strong and consistent predictor of EC. The findings highlight the necessity of suitable HR intervention for instrumentalizing personal role-organisational goal fitment to create an engaging and committed workforce. Originality/value: The study is among the few to empirically investigate the role of WS on employee commitment at work. The study is first of its kind to explore the mediating role of OCB and interactive role of EI at work in explaining the relationship between WS and EC.